Identification of a cellulolytic active fungal strain, isolated from a cigarette waste microenvironment, showing preference for growth on cellulose acetate - Enslin, Nicholas George (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.